The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4944843
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of scalable terahertz radiation from cylindrically focused two-color laser pulses in air

Abstract: We demonstrate scalable terahertz (THz) generation by focusing terawatt, two-color laser pulses in air with a cylindrical lens. This focusing geometry creates a two-dimensional air plasma sheet, which yields two diverging THz lobe profiles in the far field. This setup can avoid plasma-induced laser defocusing and subsequent THz saturation, previously observed with spherical lens focusing of high-power laser pulses. By expanding the plasma source into a two-dimensional sheet, cylindrical focusing can lead to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Currently, the most powerful table-top THz sources are based on either optical rectification in electro-optic crystals [17][18][19] or twocolor filamentation in gases and liquids [20][21][22][23][24] . With optical rectification THz pulses with energy up to 0.9 mJ 18 and THz conversion efficiency (ratio of generated THz energy to the input laser pulse energy) up to 3.7% 25 were generated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most powerful table-top THz sources are based on either optical rectification in electro-optic crystals [17][18][19] or twocolor filamentation in gases and liquids [20][21][22][23][24] . With optical rectification THz pulses with energy up to 0.9 mJ 18 and THz conversion efficiency (ratio of generated THz energy to the input laser pulse energy) up to 3.7% 25 were generated.…”
mentioning
confidence: 99%
“…Also, THz pulses generated by optical rectification are long (several picoseconds) and their spectra are narrow (below 5 THz). In turn, two-color filamentation of near infrared laser pulses offers less energetic THz pulses (up to 30 μJ in gases 22 and up to 80 μJ in liquids 24 ) with a lower THz conversion efficiency (~0.01%). Nevertheless, since the gas or liquid media recover in-between laser shots, there is no issue with the optical damage threshold.…”
mentioning
confidence: 99%
“…It is worth noting the new variety of materials on the basis of which the efficient sources of terahertz radiation are being created [10,11]. The most popular mechanism is terahertz generation via filamentation in gases with one or two-color optical excitation due to the possibility to control output radiation by the pump laser parameters [12][13][14][15]. Using two-color filamentation, maximum efficiency is around 0.01% [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xie et al [3] delivered frequency doubled beams (2ω) time delayed with respect to the original pulse beam (ω), and Peng et al [8] also used an adjustable aperture to tailor the Gaussian beam to obtain enhanced THz radiation. Another study [9] showed that the energy conversion efficiency of the second harmonic method can be improved using a cylindrical lens. This changes the focal spot and the shape of the filament, improving the structure of the photocurrent within the filament and controllability of the radiation pattern and generation efficiency.…”
Section: Introductionmentioning
confidence: 99%